PENGARUH RELIGIUSITAS TERHADAP MINAT BELI PRODUK/JASA BANK SYARIAH DENGAN SIKAP KONSUMEN SEBAGAI VARIABEL MEDIASI (STUDI PADA NASABAH BANK KONVENSIONAL DI KOTA BANDA ACEH) - Yasir Zahri, Hafasnuddin (Departemen Manajemen, 2016)
This research aims to ascertain the impact of religiusity toward purchase intention. The sample used in this study are the. Conventional bank customers who have never used the product / service Islamic Bank The used research method utilized questionnaires as the research instrument. The amount of questionnaires that had been analyzed were 100 questionnaires. Non probability sampling system had been used for sampling technique. This technique used to the unknown element profitability within the population that was selected as the sample. Partial Least Square was also used as analysis method to ascertain the impacts from involved variables. The results showed that that, (1) The Religiusity significantly takes effect to the Purchase Intention, (2) the Religiusity significantly takes effect to Costumer Attitude, (3) the Costumer Attitude significantly takes effect to Purchase Intention, (4) the Religuisity significanly takes effect to Purchase Intention mediated by Costumer Attitude as mediation variable. Keywords : Religiusity, Purchase Intention, Costumer Attitude